(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In this paper, we establish a common fixed-point theorem for six mappings in symmetric spaces with compatible mapping of type (E) and occasionally weakly compatible mappings. Our work extends the results of Rajopadhyaya et al. [23,25], Aamri and Moutawakil [2] and other similar results in semi-metric space. 2020 Mathematical Sciences Classification: 54H25, 47H10